A new methodology for the visualization of latent fingermarks on the sticky side of adhesive tapes using novel fluorescent dyes. (June 2016) - Barros, Hélio L.; Stefani, Valter
Graphical abstract: Highlights: Novel fluorescent dyes were evaluated for the detection of latent fingermarks on different types and colors of adhesive tapes. They are highly selective, sensitive and effective for fingermarks. The novel fluorescent dyes are soluble in water (green chemistry), have high thermal and photochemical stability. Our proposed method does not require complex instrumentation, or any pre- or post-treatment of the processed adhesive tapes. Abstract: Three novel fluorescent dyes were evaluated for the detection of latent fingermarks on different types and colors of adhesive tapes. Compared with the conventional reagents used to reveal latent fingermarks on these surfaces, these new fluorescent dyes have many advantages. They are highly selective to fingermarks, require only a simple procedure, do not need pre- or post-treatment, have high thermal and photochemical stability, are low in cost and use only water as a solvent. In addition, the emitted fluorescence creates a sharp contrast with the fingermark surface, meaning the fingermarks can be clearly visualized and photographed when excited with longwave ultraviolet light (365 nm).